Implementation of Accounting Education Learning Through Living Laboratory in MSMEs - Wihartanti, Liana Vivin; Nurhuda, Nurhuda; Munafi’ah, Binti (Dinamika Pendidikan, 2018)
This study aims to determine the contribution of living laboratory and examine the advantages of living laboratory in MSMEs in Madiun in learning Accounting education, to know and formulate the forms of living laboratory, and formulate living laboratory steps for MSMEs in Madiun in learning Accounting Education. This research method used descriptive-qualitative with a case study approach. The subjects of this study were students who took a course of the business feasibility study of the University of PGRI Madiun. The object of this study was MSMEs in the city of Madiun. The data source in this study consisted of primary and secondary data. The technique of collecting data used observation, interviews and document analysis. Data analysis techniques consisted of data collection, data reduction, data presentation and conclusion (verification). The contribution of living laboratory to MSMEs is that management of living laboratory activities starts from activity planning to the implementation and evaluation of living laboratory activities. The living laboratory learning process supports students’ skills. Living laboratory learning is designed and implemented based on procedures and real work standards. Learning activities of Living laboratory are in addition to achieving mastery of competencies, also emphasizing the development of soft skills that are instilled in the individual students which includes intellectual, emotional, spiritual, and social intelligence.